A REABILITAÇÃO DE PACIENTES COM DISFUNÇÕES MOTORAS OCASIONADAS PELA DOENÇA DE PARKINSON - Souza, Maxsuel Oliveira de; Soares, Jandson de Oliveira; Monteiro, Mikaele da Costa Gomes; Reis, Rosane Pereira dos; Bezerra, Daniele Gonçalves (Gep News, 2017)
Tipo de Apresentação: Pôster